Containment in the Middle East - Eilam, Ehud (Potomac Books, an imprint of the University of Nebraska Press, 2019)
Israel, Arab states, and the United States have been conducting and experiencing various kinds of containment in recent years, as part of confronting their external and/or internal enemies.